2013
DOI: 10.1037/a0031827
|View full text |Cite
|
Sign up to set email alerts
|

Dance as a subject for empirical aesthetics.

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. There may be minor differences in this draft with respect to the published version of the paper. Both authors contributed to the paper equally. Permanent repository link Dance as a subject for empirical aestheticsWe are grateful to Marcos Nadal for very useful comments and discussions on previous drafts of the paper and to dancers and choreographers (Tom Sapsford and MavinKhoo) for their help … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(109 citation statements)
references
References 112 publications
(187 reference statements)
2
102
0
5
Order By: Relevance
“…While these studies implicate temporal features when processing the aesthetics of dance, a study by Calvo-Merino, Urgesi, Orgs, Aglioti, and Haggard (2010) demonstrated that viewing static dance postures also involves brain regions associated with aesthetic processing. In their review of these studies, Christensen and Calvo-Merino (2013) find support for four different brain regions in the aesthetic processing of dance. These include the ventral premotor cortex (BA6), medial and superior regions of the posterior occipital cortex (BA18, BA19), the inferior parietal cortex (BA 39/40) and the occipitotemporal cortex (BA37).…”
Section: Overviewmentioning
confidence: 99%
“…While these studies implicate temporal features when processing the aesthetics of dance, a study by Calvo-Merino, Urgesi, Orgs, Aglioti, and Haggard (2010) demonstrated that viewing static dance postures also involves brain regions associated with aesthetic processing. In their review of these studies, Christensen and Calvo-Merino (2013) find support for four different brain regions in the aesthetic processing of dance. These include the ventral premotor cortex (BA6), medial and superior regions of the posterior occipital cortex (BA18, BA19), the inferior parietal cortex (BA 39/40) and the occipitotemporal cortex (BA37).…”
Section: Overviewmentioning
confidence: 99%
“…Low-level stimuli features of works of art trigger our attention, including shapes and tones, and other features such as symmetry and beauty [108][109][110][111][112][113][114]. Besides, the arts push boundaries, surprise, reveal, and excite both artist and spectator.…”
Section: The Arts Hypothesismentioning
confidence: 99%
“…Recent studies have shown that expert artists (an example of experts in emotional expression) have enhanced affective responses as compared to controls. For example, actors are more empathic than non-actors (Goldstein, 2009;Goldstein & Bloom, 2011;Goldstein & Winner, 2012), musicians are better at Running head: MOVEMENT EXPERTISE AND AFFECTIVE SENSITIVITY 4 recognizing vocal expressions of emotions than non-musicians (Lima & Castro, 2011), ballet dance ability is associated with trait emotional intelligence (Petrides, Niven, & Mouskounti, 2006), and participants with dance experience show a modulation of their aesthetic response to familiar movements (Kirsch, Drommelschmidt, Cross, 2013;Kirsch, Dawson, Cross, 2015; see Christensen and Calvo-Merino, 2013 for a review on dance expertise and aesthetic perception). This suggests that expertise in the arts facilitates the processing of emotional information.…”
Section: Introductionmentioning
confidence: 99%